KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK SNACK BAR BERBASIS TEPUNG AMPAS TAHU, TEPUNG KACANG MERAH (Phaseolus vulgaris L.) DAN KACANG KEDELAI (Glycine max.) - Hadad Alwi Alwi; Damat Damat; Desiana Nuriza Putri (Universitas Muhammadiyah Malang, 2021)
The use of tofu dregs flour, red bean flour and chopped soybeans alarms to enrich the fiber and protein nutrition from the snack bar. The purpose of this study was to determine the interaction and effect of the addition of tofu pulp and red bean flour with soybeans on the physicochemical and organoleptic snack bars. The research used factorial randomized block design (RBD), the first factor was the ratio of the addition of tofu pulp flour and red bean flour with treatment T1 (14%; 86%), T2 (29%; 71%), T3 (43%; 57%) and the second factor was the addition of soybeans treated with K1 (10%), K2 (20%), K3 (30%). The results of the treatment of tofu dregs flour and red bean flour showed that the ash content in the T1 treatment (14%; 86%) was 3.20%, the fiber content in the T3 treatment (43%; 57%) was 6.54%, the protein content in T1 treatment (14%; 86%) namely 5.01%, organoleptic aroma test on T1 treatment (14%; 86%) namely 5.47 (delicious) and organoleptic taste test in T1 treatment (14%; 86%) namely 5.13 (delicious). The highest yield of chopped peanut treatment was at K1 (10%), namely 46.56 N.